2012
DOI: 10.17660/actahortic.2012.961.31
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation and in Vitro Grafting Techniques to Assist the Selection of a Pistachio Rootstock From a Population of Terebinth (Pistacia Terebinthus L.) Collected in the Se of Spain

Abstract: Pistachio culture is hampered both by the difficulty of propagation by grafting varieties of interest and by the lack of a clonal selected rootstock. The application of in vitro culture techniques would allow the clonal propagation of Pistacia species, as well as to perform in-depth studies of factors affecting grafting. In vitro P. vera cultures were initiated from nodal explants, whereas cultures of P. terebinthus were initiated from in vitro-germinated seeds. The multiplication rate of both species in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Seedlings of terebinth (P. terebinthus L.) were obtained from wild mature seeds. Seeds were peeled, washed in distilled water, dried, and cold stored at 4-5°C for at least 5 months (García et al 2011a). Seeds were then sowed in forest cells containing Pindstrup substrate, a proprietary mixture of peat:perlite (Pindstrup Mosebrug S.A.E.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Seedlings of terebinth (P. terebinthus L.) were obtained from wild mature seeds. Seeds were peeled, washed in distilled water, dried, and cold stored at 4-5°C for at least 5 months (García et al 2011a). Seeds were then sowed in forest cells containing Pindstrup substrate, a proprietary mixture of peat:perlite (Pindstrup Mosebrug S.A.E.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Despite the production of rootstocks from seeds for micrografting in vitro or in vivo, P. terebinthus rootstocks were micro-propagated in vitro, and the produced micro-cuttings with and without roots were micro-grafted in vitro with in vitro scions of P. vera. Some of the successful grafted plants could be acclimatized in vivo (Lorente et al, 2011).…”
Section: In Vivo and In Vitro Micrografting Of P Veramentioning
confidence: 99%
“…The results showed that P. vera gave rise to the best stem diameter in comparison to P. terebinthus and P. khinjuk, which is crucial for holding the micro-scions. In the continuation of the P. vera micrografting, Lorente et al (2011) obtained P. terebinthus rootstocks in vitro as micro-cuttings, and rooted and unrooted ones were micro-grafted with in vitro scions of P. vera. Following 3-5 weeks, 44% of the grafted plants survived and growth continuing was noted in some of them in the greenhouse.…”
Section: Micrografting Of P Vera Onto Different Rootstocksmentioning
confidence: 99%
See 1 more Smart Citation